Perancangan Sistem Informasi Penjualan Online dan Evaluasi Penerimaan Teknologi Menggunakan Model TAM pada Toko Sepatu XYZ - Fajriyah, Nurul; Setiawan, Wawan; Duha, Tobias (Jurnal Informatika, 2025)
The development of information technology in the current digital era encourages various sectors to enhance efficiency, competitiveness, and service reach through digital transformation. One form of its implementation is the development of online product sales systems. Toko XYZ, a business engaged in shoe sales, still relies on conventional sales methods through physical stores, thus facing challenges in reaching a wider range of customers amid changing consumer behavior. This study aims to develop a website-based sales system to support the digitalization of business operations at Toko XYZ. Data collection methods included observation, interviews, and literature studies to identify system requirements. The developed e-commerce website is designed to expand market reach, facilitate transaction processes, and provide a more convenient shopping experience for customers. System evaluation was carried out using the Technology Acceptance Model (TAM) approach, with measurements conducted through a Likert scale-based questionnaire. Analysis results show that the user acceptance rate for the website reached 89%, which falls into the "strongly agree" category. These findings indicate that the implementation of a website-based online sales system can improve sales effectiveness, expand the customer base, and strengthen Toko XYZ's competitive position in the digital market.